Iraq between occupations : perspectives from 1920 to the present - Baram, Amatzia Ed; Rohde, Achim Ed; Zeidel, Ronen Ed (Palgrave Macmillan, 2010)
"This edited volume represents a re-examination of the most central issues in the history of the Iraqi nation state until the American occupation (1920-2003) and, in the light of that history, a re-evaluation of developments under the occupation (2003-2008). By re-visiting Iraq's history, the contributors are offering a fresh look at the contradictions, oscillations and development of the Iraqi nation and its sense of identity, as well as the American occupation, and are suggesting what it all may mean in terms of the future of Iraq"--Provided by publisher.